“On the radio and TV perhaps they even speak Vilnius-like”. An acoustic analysis of unstressed variables /i:/, /u:/, /e:/, /o:/, /æ:/ and /a:/ in broadcast media and Vilnius speech - Čičirkaitė, Ramunė (Taikomoji kalbotyra, 2016)
The paper focuses on the quantitative and qualitative features of the variants of unstressed variables /i:/, /u:/, /e:/, /o:/, /æ:/ and /a:/ in spontaneous broadcast media as compared with spontaneous Vilnius speech. The research also explores how the variants of the variables are located on the spectrum, whether the speaker’s type (his linguistic education) has any impact on the length and tenseness of the variants. The research was conducted using for acoustic analysis the sound analysis program PRAAT. The informants were six Vilnius city dwellers and six radio and TV hosts. The data of the Vilnius city dwellers’ speech drew on targeted sampling from the database “Vilnius speaking”. The hosts were chosen from a representative Corpus of Broadcast Media. The empirical data consists of 840 variants of unstressed variables /i:/, /u:/, /e:/, /o:/, /æ:/ and /a:/, equally selected from each speaker’s spontaneous speech. The survey has revealed that the quantitative and qualitative features of the variants of unstressed variables /i:/, /u:/, /e:/, /o:/, /æ:/ and /a:/ used in the hostsʼ spontaneous speech are very similar to those used by spontaneously speaking Vilnius city dwellers. This leads to a conclusion that Vilnius speech is more firmly entrenched in the prestigious public discourse (broadcast media) than the codified standard language. In our speech community Vilnius speech may function as a model of exemplary pronunciation, thus strengthening the role of Vilnius speech in public discourse and at the same time weakening the positions of standardisation ideology. The investigation has confirmed that phonetic features traditionally assigned to Vilnius speech are erroneously associated only with private discourse and speakers of low social status; however, these features inevitably gain their highest value when used in broadcast media.